Surgeon and patient perceptions of cure in advanced gastrointestinal malignancies: Are we on the same page?. Issue 3 (22nd May 2020) - Lafaro, Kelly J.; Li, Arthur; Rodriguez, Jenny; Clark, Karen; Loscalzo, Matthew; Wong, F. Lennie; Melstrom, Laleh G.; Warner, Susanne G.
Abstract: Background and Objectives: Effective communication is essential to complex shared decision making and is associated with improved recovery and pain control. However, patients and surgeons often have disparate expectations of treatment efficacy and perceptions of cure for advanced malignancies. This study measures correlation of patient and surgeon expectations with perceptions of cure. Methods: Our prospective study surveying surgeon‐patient dyads before and after surgical consultation was performed for advanced abdominal malignancy between July and November 2017 at a single NCI designated cancer center using electronic questionnaires. Results: Patients and surgeons' own opinions regarding surgical candidacy (Q1), chance at cure (Q2), and life expectancy (Q3) did not measurably change from pre‐ to postvisit survey as evidenced by unchanged response concordance (patients Q1 P  = .82; Q2 P  = .81; and Q3 P  = .53; surgeon responses Q1: P  = .17; Q2: P  = .32; and Q3: P  = .50). Patient and surgeon perception of likelihood of cure and of estimated life expectancy remained discordant in pre‐ and postvisit surveys (Q2: P  = .006 and Q3: P  = .03). Conclusions: These data highlight the stark differences between patient and surgeon perceptions of cure and prognosis of gastrointestinal cancers. These results prove that a larger scale study using this electronic questionnaire is feasible and important to better understand these differences and enhance shared decision making.